Thyroid dysfunction in preeclampsia and related fetomaternal outcomes - Banik, Puja; Praneshwari Devi, R. K.; Bidya, Aheibam; Tamphasana, Akoijam; Agalya, M.; Singh, Laiphrakpam Ranjit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Changes in thyroid function in normal pregnancy are well-documented but in complicated pregnancy like preeclampsia, very little is known. Studies have shown evidences of hypothyroidism in preeclampsia necessitating thyroid function tests to be done in preeclampsia. The study was done to analyze the fetomaternal outcome of preeclampsia with coexisting thyroid dysfunction. Methods: A cross-sectional analytical study was done over 18 months on 95 preeclamptic patients admitted at the antenatal ward and fetomaternal outcomes were analyzed according to thyroid status. Results: Out of 95 patients with preeclampsia, 42 (44.2%) had thyroid dysfunction. Among these 42 patients, 37 (38.9%) patients had subclinical hypothyroidism, 4 (4.2%) had overt hypothyroidism and 1 (1%) had hyperthyroidism. Severe preeclampsia was seen in 64.3% of the patients with thyroid dysfunction compared with 39.6% in euthyroid patients. The mean thyroid stimulating hormone (TSH) level was significantly higher and means free thyroxine (fT4) level was significantly lower in severe preeclampsia compared with non-severe preeclampsia. Complications like abruption, intrauterine fetal death (IUD), intrauterine growth restriction (IUGR), oligohydramnios, preterm deliveries, postpartum hemorrhage (PPH), low birth weight babies, birth asphyxia in babies and subsequent neonatal intensive care unit (NICU) admissions were significantly higher (p <0.05) in the preeclampsia patients with thyroid dysfunction in comparison with euthyroid ones. Conclusions: Hypothyroidism may be a modifiable risk factor for preeclampsia. Thyroid screening early in pregnancy may be helpful in predicting the occurrence of preeclampsia and timely thyroid hormone administration can reduce the maternal and perinatal morbidity and mortality associated with preeclampsia.